Patterns of Interaction and Integration of Palembang’s Arab-Malay Culture - Apriana; Nurhayati Dina; Fatmah (Criksetra: Jurnal Pendidikan Sejarah, 2022)
Researchers in this study raised issues regarding the pattern of interaction and integration of the Arab-Malay Palembang culture. The purpose of this study is to explain the pattern of interaction and integration of Arab-Malay culture in Palembang. The method used in this research is the historical method. The results of this study indicate that the patterns of interaction and integration of ArabMalay Palembang culture include two patterns. Researchers divide into two patterns, namely on the one hand there has been a perpetuation of culture and on the other hand there has been a process of assimilation of elements of Malay culture into Arabic culture in Palembang. The perpetuation of Arab culture in Palembang can be seen from the marriage system, in reality Arab men may marry Malay women but on the other hand Arab women cannot marry Malays. This tradition still continues today. It can be seen from the mingling of the two cultures and perspectives on the existing culture, the architectural form of the house, communication tools, cooking and drinks, rituals/ceremonials, as well as values and attitudes, and so on.